Optimalisasi Social Media Marketing menggunakan Meta Ads untuk Meningkatkan Brand Awareness pada PT Archicon Eka Rekadaya Malang - Septi Wulandari; Umi Khabibah (Indo Publishing, 2026)
This study aims to measure the improvement of brand awareness and evaluate the effectiveness of marketing campaigns through the use of Meta Ads on the Instagram account of PT Archicon Eka Rekadaya (@archiproperti). Motivated by the initial passive and stagnant condition of the account, this study employs an action research method involving three cycles of content improvement. The quality of the reel video content was evaluated using the EPIC model (Empathy, Persuasion, Impact, Communication), involving a business owner, marketing experts, digital marketing experts, and Instagram audiences. The results indicate that the advertising video content is categorized as highly effective, achieving an average EPIC score of 4.6. The implementation of a Meta Ads campaign with a brand awareness objective over two days in the Greater Malang area successfully reached 33,153 accounts and generated 33,276 impressions, exceeding the initial target by over 330% while significantly boosting audience engagement compared to pre-campaign levels. These findings conclude that the synergy between EPIC-model-based content quality and Meta Ads distribution strategy effectively transforms corporate social media into a high-impact digital marketing channel for strengthening brand awareness.